PENGARUH DOSIS NITROGEN DARI JENIS PUPUK ANORGANIK YANG BERBEDA TERHADAP LUAS DAUN DAN WARNA DAUN RUMPUT SETARIA (Setaria sphacelata) - Rossa, Fiametha; Santosa, R. Singgih Sugeng; Hidayat, Nur (ANGON: Journal of Animal Science and Technology, 2024)
The research with the title “The Effect of Nitrogen Dose From Different Types of Inorganic Fertilizers on the Leaf Area and Leaf Color of Setaria Grass (Setaria sphacelata)” was carried out at Limpakuwus Village, Sumbang District, Banyumas Regency and observations have been carried out at the Agrostology Laboratory, Faculty of Animal Husbandry, Jenderal Soedirman University. The purpose of this research was to looking for the best inorganic fertilizer which was mixed with basic fertilizer from dairy cow feces on leaf area and leaf color of Setaria grass (Setaria sphacelata). The research materials used were Setaria grass, organic fertilizer from dairy cow feces and inorganic fertilizers (Urea, ZA and NPK). The research method used was Completely Randomized Design (RAL). The dose of inorganic fertilizer given refers to the nitrogen content of urea, which is 100 kg/ha/defoliation, 200 kg/ha/defoliation, and 300 kg/ha/defoliation, then each application is mixed with organic fertilizer of 2 kg/m2/defoliation dairy cow feces or 3 kg/1,5m2/defoliation. The results of the analysis of variance (ANOVA) showed that the effect of nitrogen levels from different types of inorganic fertilizers mixed with organic fertilizer from dairy cow feces showed no significant effect on leaf area and leaf color of Setaria grass (Setaria sphacelata). The inorganic fertilizer type Zwavelzure Ammonium (ZA) with a dose of 200 produced the highest average on the leaf area of ​​53,05 cm2. The inorganic fertilizer type Urea with a dose of 100 produced the highest average of leaf color which is 43,74. The conclusion obtained was that the application of nitrogen levels in dose of 100, 200 and 300 from the inorganic fertilizer Urea, ZA and NPK mixed with organic fertilizer from dairy cow feces produced the same leaf area and leaf color.